O reservatório de Itaipu Binacional: uma análise do impacto econômico causado aos municípios paranaenses afetados territorialmente (1983–2020) - Bebber, Romano Augusto (2022)
This research had as a basic precept to deepen the studies regarding the impact caused to the municipalities of Paraná in the period 1983-2020, which had part of their territory flooded by the Itaipu reservoir, in October 1982, giving rise to several transformations in the region where they are located, Western Paraná mesoregion – transformations of both economic and social, geographic, cultural, environmental, among others, making it an interesting object of study. Regarding the objectives, this dissertation sought to estimate the economic impact caused to the agricultural pro-duction sector and to the municipal public revenues, from the taxes that would have been levied on both the agricultural products that would have been produced and the real estate that was in the place submerged. Subsequently, a comparison was developed between these values and the royalties received by municipal public enti-ties, as a way of compensating for the externalities caused. In the sequence, the economic activities that increased after the formation of the reservoir were highlight-ed, based on the number of jobs and establishments in each sector. To this end, a reconnaissance of the flooded area was undertaken, by means of spatial analysis, using the photointerpretation method and geoprocessing tools. Based on this, it was inferred that the flooded territory had a very relevant productive potential, especially in the most recent period, when the average yield of agricultural products has inten-sified. It was also observed that the estimated taxes would have earned modest val-ues, when compared to the royalties received by the municipal entities directly af-fected. Furthermore, it was verified that, from the formation of the reservoir, most of the affected municipalities experienced a very expressive expansion in the number of jobs in the industrial sector, besides some standing out in the service, commerce and public administration sectors, while the agricultural and civil construction sec-tors showed little representation in the total number of jobs in relation to the others.